RC frame structures retrofitted by FRP-wrapping: A model for columns under axial loading and cyclic bending. (15th March 2020) - Ferracuti, Barbara; Savoia, Marco; Zucconi, Maria
Highlights: A model for FRP wrapping under axial loading and cyclic bending is proposed. The model accounts for variable confinement pressure over the concrete cross-section. The model reliability is checked by comparison of numerical and experimental results. The model is implemented in an open-source finite element software (OpenSees). Different retrofitting strategies are compared with reference to a pre-code RC frame. Abstract: In order to mitigate the seismic risk of existing RC frame structures not designed with seismic criteria, a widespread strengthening strategy is based on increasing strength and ductility of RC columns by means of Fiber Reinforced Polymer wrapping. The existing models for RC cross-sections wrapped by FRP sheets were developed principally considering pure axial loads with uniform confinement pressure. In seismic areas, RC columns are instead usually subjected to axial load and cyclic bending. In the present work, in order to consider the effective loading conditions, an iterative cyclic model for square RC cross-sections wrapped by composite FRP sheets subjected to axial force and cyclic bending is proposed. The model considers the strain gradient-effect over the cross-section due to the bending loads that change significantly the confinement level of RC cross-section. Moreover, the model has been validated by comparing the numerical outcomes with various cyclic experimental results. The model has been also implemented in an open-source software with distributed plasticity finite elements in order to perform pushover analyses of an existing RC frame structure with different retrofitting strategies to improve the ductility of the columns for lateral forces.